(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate the effects of dual-tasks on balance in school-age children aged 7-10 years. Materials and Methods: In the present study, 28 primary school children aged 7-10 years were included. Static and dynamic balances were evaluated separately without any additional task and also in the presence of additional cognitive and motor tasks. The Sharpened Romberg Test and the One-Leg Stance Test were used to evaluate the static balance. The Five-Repetition Sit-To-Stand Test was used to evaluate dynamic balance. As a cognitive additional task, the children were asked to say "Yes" when they saw the red card and "No" when they saw the blue card. The motor additional task was designated as catching a ball. Results: In the static balance tests, the scores performed in the presence of an additional cognitive task were higher than those obtained without any additional task. However, this difference was not statistically significant (p>0.05). Test scores obtained with an additional motor task were significantly lower than those obtained without any additional task (p<0.001). In the Five-Repetition Sit-to Stand Test, the scores obtained in the presence of additional cognitive (p = 0.003) and motor (p = 0.002) tasks were significantly higher than those obtained without any additional task. Conclusion: In our study, an additional motor task performed simultaneously with static balance tests negatively affected balance performance in children aged 7-10 years. Postural control also reduced by additional motor or cognitive tasks during the dynamic balance tests. The results obtained in this study will contribute to understanding the relationship between cognition and balance system in children.